1989
DOI: 10.1038/342291a0
|View full text |Cite
|
Sign up to set email alerts
|

Substantial increase of protein stability by multiple disulphide bonds

Abstract: Disulphide bonds can significantly stabilize the native structures of proteins. The effect is presumed to be due mainly to a decrease in the configurational chain entropy of the unfolded polypeptide. In phage T4 lysozyme, a disulphide-free enzyme, engineered disulphide mutants that crosslink residues 3-97, 9-164 and 21-142 are significantly more stable than the wild-type protein. To investigate the effect of multiple-disulphide bonds on protein stability, mutants were constructed in which two or three stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
225
0
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(236 citation statements)
references
References 24 publications
4
225
0
5
Order By: Relevance
“…Disulfide bridges contribute to the overall stability of a protein, and the introduction of new S-S bonds can enhance the thermal stability, as demonstrated in phage T4 lysozyme (Matsumura et al 1989). EAP share five conserved cysteine residues with PRK1.…”
Section: Discussionmentioning
confidence: 99%
“…Disulfide bridges contribute to the overall stability of a protein, and the introduction of new S-S bonds can enhance the thermal stability, as demonstrated in phage T4 lysozyme (Matsumura et al 1989). EAP share five conserved cysteine residues with PRK1.…”
Section: Discussionmentioning
confidence: 99%
“…While the stability loss due to the elimination of native disulfide bonds in proteins mostly meets the expectations, the introduction of additional disulfide bonds into proteins yielded contradictory results. Various proteins in fact could be stabilized by an extra disulfide bond [56,[64][65][66][67][68] whereas others showed no effect or were even destabilized [64,[69][70][71] with a strong dependence on the position of the introduced disulfide bond [65,67]. Thus, a calculation of ∆∆G based on ∆∆S (from the tethering of the loop) only is not sufficient but hydrophobic effects of disulfide bonds and enthalpic effects on the folded protein have to be considered as well [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a calculation of ∆∆G based on ∆∆S (from the tethering of the loop) only is not sufficient but hydrophobic effects of disulfide bonds and enthalpic effects on the folded protein have to be considered as well [17,21]. Moreover, the introduction of disulfide bonds might cause 'disulfide-induced strain in the folded state' [21,56,70] and preexisting disulfide bonds impair the calculability of ∆∆S and ∆∆G [15,56]. Furthermore, extra disulfide bonds may change the folding and unfolding pathways [67] or even result in kinetic traps due to non-productive…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the enzyme was heated at 75 "C for 30 min at neutral pH, however, these cysteines were oxidized to cystine without affecting the catalytic activity of TBADH. As the results of many studies have suggested that disulfide bonds confer rigidity and stability on certain proteins (Nakamura et al, 1978;Wetzel et al, 1988;Matsumura et al, 1989;Dohlman et al, 1990;Mely & Gerard, 1990;Kanaya et al, 1991), several investigators have attempted to introduce disulfides to enhance the thermal stability of proteins, using such methods as site-directed mutagenesis (Wetzel et al, 1988;Matsumura et al, 1989;Luckey et al, 1991) or grafting cysteine-containing peptides (Magonet et al, 1992), for example. To probe the function of the cystine 283-295 disulfide in TBADH, we used site-directed mutagenesis to replace cys 283 with serine.…”
Section: Discussionmentioning
confidence: 99%